2011
DOI: 10.1007/s11745-010-3520-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Intestinal Bioaccessibility of Alkylglycerols Versus Triacylglycerols as Vehicles of Butyric Acid

Abstract: Butyric acid has been the subject of much attention last years due to its bioactivity. However, the potential advantages of butyrate are limited by the problem to reach enough plasma concentrations; therefore, pro-drugs have been proposed as an alternative to natural butyrate. A comparative study on in vitro intestinal digestion of 2,3-dibutyroil-1-O-octadecyl glycerol (D-SCAKG) and tributyrin (TB), as potential pro-drugs of butyric acid, was performed. Aliquots were taken at different times of digestion for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Torres et al [116] have recently synthesized structured alkyldiacylglycerols containing residual short-chain fatty acids at sn-2 and sn-3 locations by enzymatic transesterification of 1-O-Octadecyl glycerol and ethyl butyrate. The potential bioaccessibility of this synthetic alkylglycerol was later assayed by simulating the intestinal digestion of the molecule by pancreatic enzymes under in vitro conditions [117]. This study showed that the suggested bioactive structure of 1-O-alkyl-sn-glycerol retaining a short-chain residue was produced after intestinal hydrolysis as the major hydrolysis product, in the form of 2-butyroil-1-O-octadecyl glycerol.…”
Section: Alkylglycerols As Lipid Delivery Systems Of Bioactive Ingredmentioning
confidence: 99%
See 1 more Smart Citation
“…Torres et al [116] have recently synthesized structured alkyldiacylglycerols containing residual short-chain fatty acids at sn-2 and sn-3 locations by enzymatic transesterification of 1-O-Octadecyl glycerol and ethyl butyrate. The potential bioaccessibility of this synthetic alkylglycerol was later assayed by simulating the intestinal digestion of the molecule by pancreatic enzymes under in vitro conditions [117]. This study showed that the suggested bioactive structure of 1-O-alkyl-sn-glycerol retaining a short-chain residue was produced after intestinal hydrolysis as the major hydrolysis product, in the form of 2-butyroil-1-O-octadecyl glycerol.…”
Section: Alkylglycerols As Lipid Delivery Systems Of Bioactive Ingredmentioning
confidence: 99%
“…It has been stated that efficient pro-drugs of butyrate should have a sufficiently stable bond between the carrier and butyrate residue to increase its in vivo half-life [118]. In the performed in vitro intestinal digestion study [117], it was shown that the traditional tributyrin proposed as pro-drug of butyrate was completely hydrolyzed to butyric acid, in contrast to the obtained stable esterified form of butyric acid as 2-butyroil-1-Ooctadecyl glycerol, showing the potential of this synthetic molecule as carrier of butyrate.…”
Section: Alkylglycerols As Lipid Delivery Systems Of Bioactive Ingredmentioning
confidence: 99%
“…Diacylglyceryl ethers (DAGE) and monoacylglyceryl ethers (MAGE) have been reported in several marine animals, such as in the livers of dogfish and shark [ 7 ] and deep-sea squids ( Berryteuthis magister ) [ 8 ]. In the last two decades, ether lipids have attracted the interest of researchers due to their health promoting effects in humans, specifically for their potential in cancer therapy but also because they have been used to improve the bioavailability of other lipid molecules such as butyric acid or omega-3 FA [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune stimulators properties have also been attributed to dietary ingestion of these substances (Palmblad, Samuelsson & Brohult, 1990). In addition, recent studies indicate the these compounds could improve the bioavailability of othe lipid molecules such as butyric or omega-3 fatty acids (Martín, Morán-Valero, Señoráns, Reglero & Torres, ;Torres, Vázquez, Señoráns & Reglero, 2009).…”
Section: Introductionmentioning
confidence: 99%